Wireless Network Communication in the XML Metadata Storage of Wushu Historical Archives - Xin Liu (Hindawi-Wiley, 2021)
The wireless communication network has a huge promotion effect on data processing. As an important standard for internet data transmission, XML markup language is currently widely used in the internet. The rapid development of XML has brought fresh blood to the research of database. This article is aimed at studying the application of wireless network communication in the storage of the XML metadata database of Wushu Historical Archives. One part uses data load-balancing algorithms and two-way path constraint algorithms to conduct research on the metadata storage of XML databases, such as document size, document loading, and document query. Combining wireless technology and comparing with SGML and HTML, it highlights the flexibility and importance of XML database. The other part analyzes the XML database of Wushu Historical Archives itself and uses questionnaire surveys combined with the experience of 30 users randomly checked to provide constructive suggestions for the construction of XML database, such as strengthening the operation page design, text, and graphics. The experimental results show that the time consumed by the XML database in the case of bidirectional path indexing is 0.37 s, and the time consumed in the case of unidirectional path indexing is 0.27 s. This data shows that the application of wireless network communication technology has played an important role in the easy update and flexibility of the XML database. The data load capacity presented by the two path indexes is inconsistent; the current experience of XML database mainly focuses on the copy of the database quantity.